Classification of radial solutions arising in the study of thermal structures with thermal equilibrium or no flux at the boundary - Castro, Alfonso, 1950- (Memoirs of the American Mathematical Society, 2010)
Radial solution, unstable solution, stable solution, thermal structure, free boundary problem, ground states, equilibrium temperature.